THE CONCEPT OF ISYQ REFLECTED IN MRS GUMP’S TEACHING IN MOVIE ENTITLED FORREST GUMP - BALYA, RIFKI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Existentialism, Theistic Existentialism, Concept of IsyqHistorically, existentialism has emerged in the early 19th century. It appears as amovement of thought that opposes rationalism and intellectualism regime with deep roots in Western philosophy. Spirit of freedom is the soul of existentialism.Existentialism itself has two main branches, Atheistic and Theistic. The main difference is atheistic existentialism refuses God for human freedom, while theistic existentialism believes that by accepting the God, human beings can get their freedom. Theistic existentialism theory covers two main points, which are acceptance of God in freedom and concept of isyq and sawal. It explains about the existence of God as an individual with the creative activity, the existency of human as a free and responsible individual, and the existency of God which is not an obstacle for human’s freedom. Isyq is a condition of a human being which follows his freedom and does not give up in any condition, while Sawal is a condition of a human being which escapes from his freedom and gives up to the condition without any struggle. Based on those backgrounds, the writer wants to focus the study on the isyq concept which are reflected in Mrs.Gump’s teaching and its influence to Forrest’s life from the movie entitled Forrest Gump. From Mrs.Gump’s teaching, it can be seen that the concept of Isyq is reflected on it. That reflection and also its manifestation in Forrest’s life are interesting to analyze.In the study, the writer uses Alim Ruswantoro (2004) Theory related with the concept of isyq. The study shows that the concept of isyq reflected in Mrs. Gump’s way in teaching Forrest Gump. Mrs. Gump teaches Forrest that existency of God as an individual with creativity is not an obstacle for human existency, and a human being has his freedom to act, and never give up in any condition. The concept of Isyq theory that reflected in Mrs. Gump’s way of teaching makes Forrest to be able to achieve the same thing as the other normal people and show his existence to the world.The writer suggest the next researchers to analyze The concept of isyq in other media, such as in novel or poetry. The writer also hopes the next researchers add any other theories in existentialism to enrich the knowledge for those who read the thesis.